GLIDER MODEL FLYING DYNAMICS SIMULATION EAGE-X ON LONGITUDINAL MATRA - Retnowati, Nurcahyani Dewi; Junaidin, Buyung; Rande, Engelbertus (Vortex, 2022)
The Glider Eagle-X aircraft is an unmanned aircraft which is expected to fly with a height of 7 meters above the ground in Yogyakarta (120 m above sea level) with a flying speed of 10 m/s. In order for the Eagle-X glider to fly stably, it is necessary to analyze the flight stability of the Eagle-X glider model. Therefore, in this study, the analysis phase of static stability and dynamic response of disturbances in the longitudinal dimension was carried out. This can be useful for students so that they can better understand the analysis of static stability and dynamic response of disturbances in the longitudinal dimension. The results of the analysis show that the flight dynamics is a value of CM-α < 0 indicating the plane is statically longitudinal and the initial response of the graph is getting smaller which indicates the plane's motion is dynamically stable. The output of the stability analysis of the flying dynamics of the Eagle-X glider model is in the form of a graph. The simulation of the flying dynamics of the Eagle-X glider in the expected longitudinal dimension is shown by the aircraft movement following the graph from the results of the stability analysis which is used as the path of the Eagle-X glider model.